1993
DOI: 10.1007/bf00919031
|View full text |Cite
|
Sign up to set email alerts
|

Primary vitrectomy for rhegmatogenous retinal detachment

Abstract: One hundred and twenty-four eyes with a rhegmatogenous retinal detachment, considered to be at high risk of failure if treated conventionally, underwent vitrectomy and internal tamponade, with or without scleral buckling, as the primary procedure. The retina was reattached in 64.5% of eyes after one operation, 75.0% after two, and in 83% of eyes after more than two operations, with no difference in the success rate between those eyes which underwent vitrectomy alone, and those that received adjunctive scleral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(61 citation statements)
references
References 12 publications
2
55
0
4
Order By: Relevance
“…In yet another study, El-Rayes reported success rates of 85.71 and 94.62% in treating retinal detachment in high myopes with scleral buckling and pars plana vitrectomy, respectively (American Academy Ophthalmology Subspecialty Day, Retina, 2003, Anaheim, LA, USA). Comparing the postoperative results ranging from 64.5 to 88.0% in other reports, [23][24][25][26] in patients with all kinds of refractive error, the anatomical success rate was quite favourable in highly myopic eyes despite the high risk and difficulty in vitreoretinal surgery.…”
Section: Discussionmentioning
confidence: 76%
“…In yet another study, El-Rayes reported success rates of 85.71 and 94.62% in treating retinal detachment in high myopes with scleral buckling and pars plana vitrectomy, respectively (American Academy Ophthalmology Subspecialty Day, Retina, 2003, Anaheim, LA, USA). Comparing the postoperative results ranging from 64.5 to 88.0% in other reports, [23][24][25][26] in patients with all kinds of refractive error, the anatomical success rate was quite favourable in highly myopic eyes despite the high risk and difficulty in vitreoretinal surgery.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, the rates of postoperative PVR development [22][23][24] and anatomical success 4,7,12,15,[22][23][24][25] are in accordance with published data, although we found the differences in the latter between phakic and pseudophakic eyes to be somewhat smaller than those reported by other investigators. 24,26,27 One reason for the small difference in anatomical outcome between phakic and pseudophakic eyes could be that previous studies included predominately scleral buckling procedures without vitrectomy, or included eyes that were either aphakic, had received an anterior chamber lens or did not qualify for uncomplicated posterior chamber lens implantations. 4,6,7,16,17,22,23,25 The situation of the implant has already been shown to have an impact on the anatomical and functional outcome of reattachment surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] The minimum acceptable standards that the steering committee felt should be achieved are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%